Compact portable multiphoton microscopy reveals histopathological hallmarks of unprocessed lung tumor tissue in real time. Issue 4 (21st August 2020) - van Huizen, Laura M. G.; Radonic, Teodora; van Mourik, Frank; Seinstra, Danielle; Dickhoff, Chris; Daniels, Johannes M. A.; Bahce, Idris; Annema, Jouke T.; Groot, Marie Louise
Abstract: During lung cancer operations a rapid and reliable assessment of tumor tissue can reduce operation time and potentially improve patient outcomes. We show that third harmonic generation (THG), second harmonic generation (SHG) and two‐photon excited autofluorescence (2PEF) microscopy reveals relevant, histopathological information within seconds in fresh unprocessed human lung samples. We used a compact, portable microscope and recorded images within 1 to 3 seconds using a power of 5 mW. The generated THG/SHG/2PEF images of tumorous and nontumorous tissues are compared with the corresponding standard histology images, to identify alveolar structures and histopathological hallmarks. Cellular structures (tumor cells, macrophages and lymphocytes) (THG), collagen (SHG) and elastin (2PEF) are differentiated and allowed for rapid identification of carcinoid with solid growth pattern, minimally enlarged monomorphic cell nuclei with salt‐and‐pepper chromatin pattern, and adenocarcinoma with lipidic and micropapillary growth patterns. THG/SHG/2PEF imaging is thus a promising tool for clinical intraoperative assessment of lung tumor tissue. Abstract : A portable label‐free real‐time ex‐vivo microscope is used to investigate fresh unprocessed lung tumor tissue by generating third harmonic generation (THG), second harmonic generation (THG) and two‐photon excited fluorescence (2PEF) images, and comparing those images with standard HE histology images. Cellular structures (THG), and collagen (SHG) and elastin (2PEF) fibers can be distinguished, revealing important histopathological hallmarks (cell morphology and tissue architecture) for the assessment of lung tumor tissue.